Analisis Manajemen Risiko Berbasis ISO 31000 Untuk Mengelola Risiko Operasional Di Bidang X Pada Perusahaan Dinas XYZ - Fauzia Zalnya Putri; Iriani (CV. ITTC INDONESIA, 2023)
This research aims to determine the implementation of risk management based on ISO 31000 and identify all possible risks that occur in operational activities in field technical answer. In this study, there were 24 types of risks in field X. From the identification results, there were 4 risks at a low level, 14 risks at a moderate level and 6 risks at a high level. The benefit of this research is to provide results and evaluation of possible risks that occur in field X in order to increase the effectiveness of handling risk management based on ISO 31000.